4
$\begingroup$

Let $f$ be a differential function satisfying the relation $f(x+y)=f(x)+f(y) - 2xy + (e^x -1)(e^y -1)$$ \ \forall x , y \in\mathbb R $ and $f'(0)=1$

My work

Putting $y=0$ $$f(x)=f(x) + f(0)$$

$$f'(x)=\lim_{h\to 0} \frac{f(x+h)-f(x)}{h}$$ $$f'(x)=\lim_{h\to 0} \frac{f(x)+f(h) - 2xh + (e^x -1)(e^h -1)-f(x)}{h}$$ $$f'(x)=\lim_{h\to 0} \frac{f(h) - 2xh + (e^x -1)(e^h -1)}{h}$$ How to predict things after that?

$\endgroup$
4
$\begingroup$

As $f$ is differentiable, $$ \lim_{h \to 0} \frac{f(h)}{h}=f'(0)=1 $$ Also, $$\lim_{h \to 0} \frac{-2xh+(e^x-1)(e^h-1)}{h}=-2x+(e^x-1)\lim_{h \to 0} \frac{e^h-1}{h}=-2x+e^x-1$$

Putting this together, $$ f'(x)=1-2x+e^x-1=-2x+e^x $$ and you can integrate to find $f$.

$\endgroup$
4
$\begingroup$

Alternatively, write the functional equation as $$f(x+y)-e^{x+y}+(x+y)^2+1=f(x)-e^x+x^2+1 + f(y) - e^y +y^2+1$$

Substitute $g(x)=f(x)-e^x+x^2+1$. This gives

$$g(x+y)=g(x)+g(y)$$

which is the Cauchy functional equation. Because $f$ is differentiable at zero, all solutions are given by $g(x)=cx$ for some $c \in \mathbb R$.

So $f(x)=e^x+cx-x^2-1$. So $f'(x) = e^x+c-2x$, so $f'(0)=1+c=1$, hence $c=0$.

So $f(x)=e^x-x^2-1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.